Electroacupuncture improves scopolamine hydrobromide induced dry eye in mice via inhibiting ocular surface inflammation and regulating the HMGB1-related signaling pathways - Wu, Xia; Ding, Ning; Liang, Shangjie; Han, Yutong; Fan, Siyuan; Wu, Yunchuan; Wei, Qingbo (Frontiers in Medicine, 2025)
ObjectiveThis study aims to observe the effect of Electroacupuncture (EA) on improving ocular surface inflammation and HMGB1-related signaling pathways in dry eye disease (DED). Methods: Healthy male C57BL/6 J mice were treated with scopolamine hydrobromide for 21 consecutive days to establish the animal models for DED. After 21 days, fluorometholone (Flu), EA, and sham EA (Sham) treatments were performed. The effect of EA on DED surface inflammation was evaluated by corneal fluorescence staining, phenol red thread test, in vivo confocal microscopy (IVCM), and corneal histopathology. The influence of EA on high-mobility group box 1 (HMGB1), receptor for advanced glycation end products (RAGE), toll-like receptor 2 (TLR2) and toll-like receptor 4 (TLR4) was assessed by immunohistochemistry, real-time quantitative polymerase chain reaction (RT-qPCR), and western blot. The influence of EA on interleukin-6 (IL-6) and interleukin-10 (IL-10) were measured by enzyme-linked immunosorbent assay (ELISA).ResultsEA can significantly increase tear flow and reduce corneal staining and corneal stromal inflammation, while also improving the morphologic structure of the cornea and lacrimal glands. The levels of HMGB1, RAGE, TLR2, TLR4, and IL-6 were significantly decreased while IL-10 level was significantly increased after EA treatment, indicating that EA may improve dry eye surface inflammation by inhibiting HMGB1-related signaling pathways.ConclusionThe findings presented in our study demonstrate that EA may improve ocular surface inflammation in mice with DED by inhibiting the HMGB1-related signaling pathways. Therefore, EA may be a potential therapeutic target for DED.